Pembelajaran PAI Berbasis Video dalam Meningkatkan Akhlak Mulia - Tengku Nabilah Chalil (UNISBA Press, 2024)
Abstract. Moral education is expected to build the character of groups, congregations and people through collaboration between schools and parents. SDN 084 Cikadut is committed to providing quality education for all students regardless of economic background. The use of video-based learning is currently in the spotlight, because it can stimulate children's interest and help form morals and moral values. Video based learning can be an effective solution in instilling moral values, especially akhlakul karimah. The video shows presented are easy to understand and can be implemented by students in everyday life. This research aims to analyze the planning, implementation, results, as well as supporting and inhibiting factors for video based learning in improving the morals and morals of students at SDN 084 Cikadut, using a qualitative approach. Researchers use descriptive research methods to analyze, describe and summarize the conditions or problems studied through collecting data from interviews and observations. SDN 084 Cikadut applies video based learning and habituation to improve students' morals and morals. Supporting and inhibiting factors in implementing this learning include aspects of video content, students, and facilities and infrastructure. Supporting factors for video content include: (1) a variety of video sources, such as animation and humans, (2) all videos display at least one moral value, and (3) diversity of material that offers many choices. Abstrak. Pendidikan Akhlak diharapkan dapat membangun karakter kelompok, jamaah, dan umat melalui kolaborasi antara sekolah dan orang tua. SDN 084 Cikadut berkomitmen memberikan pendidikan berkualitas bagi semua peserta didik tanpa memandang latar belakang ekonomi. Penggunaan pembelajaran berbasis video saat ini menjadi sorotan, karena dapat merangsang minat anak-anak dan membantu pembentukan akhlak serta nilai-nilai moral. Video based learning dapat menjadi solusi efektif dalam menanamkan nilai-nilai akhlak, khususnya akhlakul karimah. Tayangan video yang disajikan mudah dipahami dan dapat diimplementasikan oleh peserta didik dalam kehidupan sehari-hari. Penelitian ini bertujuan menganalisis perencanaan, pelaksanaan, hasil, serta faktor pendukung dan penghambat pembelajaran video based learning dalam meningkatkan akhlakul karimah peserta didik SDN 084 Cikadut, dengan menggunakan pendekatan kualitatif. Peneliti menggunakan metode penelitian deskriptif untuk menganalisis, menggambarkan, dan merangkum kondisi atau masalah yang diteliti melalui pengumpulan data dari wawancara dan observasi. SDN 084 Cikadut menerapkan video based learning dan pembiasaan untuk meningkatkan akhlakul karimah peserta didik. Faktor pendukung dan penghambat dalam implementasi pembelajaran ini meliputi aspek konten video, peserta didik, serta sarana dan prasarana. Faktor pendukung konten video meliputi: (1) variasi sumber video, seperti animasi dan manusia, (2) semua video menampilkan minimal satu nilai akhlakul karimah, dan (3) keberagaman materi yang menawarkan banyak pilihan.